dNTP versus NTP discrimination by phenylalanine 451 in duck hepatitis B virus P protein indicates a common structure of the dNTP-binding pocket with other reverse transcriptases - Beck, Jürgen (Oxford University Press, 2002)
Hepatitis B viruses, or hepadnaviruses, are small DNA-containing viruses that replicate through reverse transcription. Their prototype, HBV, causes severe liver disease in humans. The hepadnaviral P protein is an unusual reverse transcriptase (RT) that initiates DNA synthesis by host-factor-dependent protein priming on a specific RNA stem–loop template, ɛ, yielding a short DNA oligonucleotide covalently attached to the RT. This priming reaction can be reconstituted with in vitro-translated duck hepatitis B virus (DHBV) P protein. No direct structural data are available for any P protein. However, P proteins share a number of conserved motifs with other polymerases. Box A contains an invariant bulky residue recently shown to be crucial for dNTP versus NTP discrimination in RTs and some DNA polymerases; its equivalent in DHBV P protein would be phenylalanine 451 (F451). Four mutants, containing glycine (F451G), alanine (F451A), valine (F451V) and aspartate (F451D), were therefore analyzed for their ability to utilize dNTPs and NTPs in in vitro priming. Priming efficiencies with dNTPs decreased with decreasing side chain size but GTP utilization increased; the wild-type enzyme was inactive with GTP. In the context of complete DHBV genomes, all mutant proteins were competent for RNA encapsidation, indicating the absence of global structural alterations. Because the function of the discriminatory residue depends on its specific spatial disposition this strongly suggests a similar architecture for the P protein dNTP-binding pocket as in other RTs.